Achromobacter xylosoxidans/denitrificans bacteremia and subsequent fatal Escherichia coli/Streptococcus anginosus pleural empyema - Habib, Saad (Respir Med Case Rep, 2018)
Achromobacter xylosoxidans, a gram-negative bacillus with low virulence has rarely been reported to cause clinically significant infections. We report an unusual case of MDR Achromobacter xylosoxidans/denitrificans bacteremia from a peripherally inserted central catheter (PICC) and subsequent fatal pleural empyema due to MDR Escherichia coli and Streptococcus anginosus. A 44-year-old male presented to the hospital with chief complaints of chest tightness associated with a productive cough. He was found to have pleural empyema secondary to MDR E. coli and S. anginous. Three months prior to current presentation, he had a history of MDR A. xylosoxidans originating from a PICC. The patient expired even after appropriate management. Thoracic empyema continues to cause significant morbidity and mortality despite the improvement of antimicrobial therapy and the existence of multiple options for drainage of the infected pleural space. The bacteriology of thoracic empyema has been changing since the introduction of antibiotics. Typical antibiotics used to treat these MDR pathogens have become obsolete. Therefore, physicians should be aggressive in their diagnostic approach to pleural empyema, since the isolation of MDR aerobic gram-negative bacilli or multiple pathogens from the pleural fluid is associated with a poor prognosis and indicates a need for more aggressive antimicrobial chemotherapy. Also, the association of indwelling medical devices and MDR Achromobacter bacteremia should be known.